2020
DOI: 10.1186/s42522-020-00028-1
|View full text |Cite
|
Sign up to set email alerts
|

Spillover of ebolaviruses into people in eastern Democratic Republic of Congo prior to the 2018 Ebola virus disease outbreak

Abstract: Background The second largest Ebola virus disease (EVD) outbreak began in the Democratic Republic of Congo in July 2018 in North Kivu Province. Data suggest the outbreak is not epidemiologically linked to the 2018 outbreak in Equateur Province, and that independent introduction of Ebola virus (EBOV) into humans occurred. We tested for antibodies to ebolaviruses in febrile patients seeking care in North Kivu Province prior to the EVD outbreak. Methods Patients were enrolled between May 2017 and April 2018, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
4
0
2
Order By: Relevance
“…Others have suggested that over a ve-year period, persistence of GP-speci c antibody responses is over 75% and 67% for at least two antigens 19 . Regarding the possibility of exposure to non-EBOV loviruses, the GP of Ebolaviruses is highly cross-reactive between species although the magnitude of GP antibody binding varies between Ebolavirus species 17,31 . EBOV convalescent sera exhibits pan-species neutralisation though the proportion of individuals exhibiting cross-species neutralisation also varies dependent on infecting strain 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that over a ve-year period, persistence of GP-speci c antibody responses is over 75% and 67% for at least two antigens 19 . Regarding the possibility of exposure to non-EBOV loviruses, the GP of Ebolaviruses is highly cross-reactive between species although the magnitude of GP antibody binding varies between Ebolavirus species 17,31 . EBOV convalescent sera exhibits pan-species neutralisation though the proportion of individuals exhibiting cross-species neutralisation also varies dependent on infecting strain 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, before the Kivu Ebola virus disease outbreak in the Democratic Republic of the Congo (July, 2018, to June, 2020), a team of researchers found 10% Ebola virus seroprevalence in samples collected from the region from May, 2017, to April, 2018, indicating a risk of outbreaks in the area; the results were published in November, 2020. 23 Animal surveillance can also indicate that particular populations or areas face spillover risk, especially if viruses of concern are being detected in animals (and serological evidence indicates human exposure) at high-risk interfaces such as wildlife markets and supply chains, [24][25][26] or in domesticated animals. 13,[27][28][29] Thanks to methodological advances in experimental virology 30,31 and computational biology, 12,32,33 some wildlife viruses can even be identified as potential threats before the first known case of human infection, and gaps in countermeasures can also be assessed.…”
Section: Limitationsmentioning
confidence: 99%
“…Todos, exceto o REBOV, foram detectados apenas na África. O REBOV foi isolado, em 1990, em Reston (EUA), de macacos importados das Filipinas (GOLDSTEIN et al, 2020;GUMUSOVA;SUNBUL;LEBLEBICIOGLU, 2015;SINGH et al, 2017).…”
Section: Etiologia Da Doença Pelo Vírus Ebolaunclassified
“…Com diferenças na patogenicidade, todas as espécies de vírus ebola, exceto provavelmente a BOMV, são associados à febre hemorrágica em humanos e primatas não humanos humanos (GOLDSTEIN et al, 2020). A estirpe REBOV é fatal para macacos, mas não é patogênica ou tem baixa patogenicidade para humanos, enquanto as estirpes ZEBOV e SEBOV têm alta virulência e elevada taxa de letalidade em humanos (SINGH et al, 2017).…”
Section: Patogêneseunclassified